The pursuit of curriculum : schooling and the public interest - Reid, William Arbuckle (Research in curriculum and instruction., 2006)
In this far-reaching discussion of curriculum and liberal education, William A. Reid compares curriculum making to the idea of "pursuit." Like justice, Reid argues that curriculum is not something that we own or possess in a material sense; rather, it is an achievement that anyone involved in schooling must and should pursue. Drawing upon the acclaimed work of Joseph J. Schwab, Reid discusses four traditions within curriculum theory (the systematic, the radical, the existentialist, and the deliberative), and then makes his case that a deliberative perspective is the soundest, most long-lasting philosophical tradition for curriculum theorists to follow. Reid's goal is to persuade readers to engage in the age-old practice of deliberation. Wesley Null introduces readers to Reid's book with a new introduction and postscript that connect the Schwab-Reid tradition to the ancient roots upon which deliberative theory is based. Null also draws connections between Reid's text and contemporary issues facing curriculum and education in 21st century America. In a world in which passion-driven arguments for extreme views on curriculum often dominate discussions, Reid's book offers a balanced perspective that is rooted in reason, wisdom, and a deep-seated commitment to justice and the public good. This book speaks directly to teachers, school administrators, university faculty, and anyone else who is interested in thinking clearly about the question of what should be taught in America's schools.